Factors Affecting Tax Compliance of MSMEs in Dipolog City - Granfon, Janven A.; Lagare, Wella Nova Joy D.; Aling, Dexter A.; Dangcalan, Neil Bryan D.; Ebanay, Ara A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This research is made focused on assessing what factors could affect the tax compliance of MSMEs in Dipolog City, one of the major economic drivers are; (1) Tax Inspection Possibility, (2) Tax Rates, (3) Tax Penalties, (4) Tax Policies Complexity, (5) Social Norms and (6) Tax Knowledge. Through random sampling, 96 business owners/managers/bookkeepers of specifically retail MSMEs in Dipolog City were extracted as respondents. A descriptive correlational quantitative method was used in this study, utilizing standardized adapted questionnaires for gathering data which was analyzed and interpreted using frequency, percentage distribution, mean, Kruskal-Wallis test, and Spearman Rho. Findings revealed most of the enterprises belong to a micro level and are still in the business for 2-5 years. Furthermore, among the factors identified, only Tax inspection Possibilities, Tax Penalties, and Tax Knowledge have significant relationships with tax compliance. This means that the possibility of being inspected, delayed payment of obligations, and their knowledge of tax laws increased the respondents’ awareness of tax compliance. If a taxpayer has knowledge about tax laws, payments, and tax rates applied to his/her business, compliance increases. It is also recommended that the taxing authority must conduct a statutory tax seminar to MSMEs as taxpayers.